Analgesic efficacy of a single dose intrathecal morphine in patients undergoing robot-assisted laparoscopic prostatectomy (RALP) (UCC Student Medical Journal, 2026)
Background: The World Federation of Societies of Anaesthesiologists has established guidelines for anaesthesia in laparoscopic surgery, but detailed protocols for perioperative pain management in Robot-Assisted Laparoscopic Prostatectomy (RALP) are lacking (1). This study evaluated the analgesic efficacy of a single intrathecal morphine (ITM) dose in RALP.Methods: Following Ethics Committee approval, a retrospective chart review of 79 patient charts that underwent RALP procedures between 01/01/2021 and 31/05/2023 was conducted. One patient was excluded due to regular codeine use. Patients were divided into ITM (n=18) and non-ITM (NITM, n=60). Outcomes included recovery room pain scores, opioid requirements, time to first opioid request, 24-hour postoperative opioid consumption, opioid-related side effects, and anti-emetic usage. Data was analyzed using SPSS, with P
Keywords: Spinal anaesthesia; robot-assisted laparoscopic prostatectomy; pain management